Positive and negative factors for the treatment outcomes following total ankle arthroplasty? A systematic review. Issue 1 (January 2020) - Zhao, Dahang; Huang, Dichao; Zhang, Gonghao; Wang, Xu; Zhang, Tiansong; Ma, Xin
Highlights: Patient selection, surgeon's experience and implant design play an integral role and affect the treatment outcomes of total ankle arthroplasty. Some positive and negative factors for different clinical and radiographic outcomes were found based on multilevel mixed-effects logistic regression anaylsis. These factors should be taken into consideration in clinical practice and ankle implant design. Abstract: Background: Patient selection, surgeon's experience and implant design play an integral role and affect the treatment outcomes of total ankle arthroplasty (TAA). The aims of this study were to investigate the positive and negative attributes that correlate with different clinical and radiographic outcomes. Methods: Eight-nine studies matched the inclusion criteria: (1) studies of primary TAA with uncemented prosthesis; (2) mean follow-up of no less than 2-year; (3) reports of clinical and radiographic outcomes, and exclusion criteria: (1) non-English study; (2) more than one type of prosthesis without separated data; (3) kin studies with shorter follow-up or smaller cohort. Age, etiology, preoperative deformity, surgeon's experience, follow-up duration and prosthetic type were studied with respect to different outcomes by mixed-effects logistic regression analysis. Results: Patients factor: older patients reported less pain or stiffness and demonstrated less radiographic loosening which did not require additional surgical intervention. More traumatic arthritis experienced adjacent joints degeneration after TAA. Surgeon factor: less experienced surgeons had more intraoperative complications. Lack of experience for complications management without implant retrieval during early period might result in more revisions or fusion was done. Prosthetic factor: updated instrumentation decreased malalignment. If the polyethylene (PE) insert was significantly narrower than the metal components more implant instability and subsequent severe particulate wear was seen. Designs with flat-on-flat articulation and ridge at the center of the talar component associated with more PE fracture. Minimal bone resection reduced postoperative fractures. A flat cut of the tibial component and a flat undersurface with press-fit by two screws or pegs of the talar component demonstrated less postoperative fractures, whereas a syndesmosis fusion and a small triangular shape with one central fin of the talar component experienced more loosening which did not require additional surgery. Anatomic conical shape of the talar component seemed to reduce adjacent joint degeneration. Finally, fewer failures were found in patients who received HINTEGRA and Salto Talaris. Conclusions: Based on our investigation, some positive and negative factors for different clinical and radiographic outcomes were found, which should be taken into consideration in clinical practice and ankle implant design.